Informal-formal linkages in market and street trading in Accra - Anyidoho, N.A.; Steel, W.F. (My University, 2016)
This paper investigates the ways in which linkages between the informal and formal segments of an economy may yield benefits to or impose costs upon informal workers, based on views of informal traders in Accra regarding their relationships with the formal economy and its institutions. The data are drawn from the Informal Economy Monitoring Study (IEMS), with a World Bank study of informal household enterprises providing context for the IEMS-Ghana study and a basis for interpretation of its ndings. Data from 15 focus groups and a survey of 150 traders from both central and non-central locations of Accra, Ghana, are analysed in terms of traders’ relationship to the value chain, non-go-vernment institutions, government and the macroeconomy. The last two are found to exert a strong, mostly negative inuence on informal operators, offset to some extent by support from member-based organizations and non-govern-mental organisations (NGOs). Access to loans from micronance institutions was an important inuence on traders’ work and was viewed both positively and negatively. Although there are few visible direct linkages between informal operators and formal rms, they are to some extent mutually interdependent as retailers and suppliers in the value chain. Taking advantage of the potential synergy in informal-formal linkages will require government and other actors to become more proactive in facilitating, rather than denying, infrastructure, sup-port services and adequate space for informal traders. The probability of such an outcome depends on the ability of informal traders to organise themselves.
Keywords: Informal economy; Informal-formal linkages; Market traders; Street vendors; Ghana